Conference Scene: Wake-up call for the engineering and biomedical science communities in nanomedicine. (July 2009) - Beck, Dominik; Wong, Stephen TC
The IEEE-NIH 4th Life Science Systems and Applications Workshop 2009 (LiSSA ''09) was jointly organized by the IEEE LiSSA Technical Committee and the NIH Nano Task Force. It was endorsed by the NIH Biomedical Information Science and Technology Initiative (BISTI) and the National Library of Medicine. The workshop was held in the Natcher Conference Center on the NIH campus in Bethesda, MD, USA. It took place on the 9––10 April, 2009, during the NIH NanoWeek and had approximately 200 delegates from around the globe (including North America, Europe, Asia and Australia) from both engineering and biomedical science disciplines. The conference featured around 40 talks, including nine plenary speakers emphasizing current state-of-the-art nanotechnology practices, developments and industry applications. All talks were scheduled in three oral and seven special sessions, as well as three breakout sessions. In addition, the interactive poster sessions hosted over 30 abstracts and attracted much attention from the audience; these sessions were readily used by many attendees to connect with colleagues of similar interest. In this article, we provide some of the highlights from the workshop.